Journalists and Media Ownership: Practices and Professional Conditions of Argentine Journalism - Amado, Adriana; Waisbord, Silvio (Brazilian journalism research, 2018)
The professional practices of Argentine journalists reveal the multiplicity of factors that impact journalistic culture. The results of the national study for the global project Worlds of Journalism offers evidence that the type of media organization in which journalists work does not generate different working conditions or respond to alternative professional models. The results reinforce the approach that the professional culture is the result of the interaction between personal values and the guidelines of organizations and companies. In this sense, the study of the professional culture of journalism needs to be approached from a multidimensional perspective that includes the study of legal frameworks, trade union protection, organizational guidelines and accepted ethical parameters. As práticas profissionais dos jornalistas argentinos mostram a diversidade de fatores que impactam na cultura jornalística. Os dados nacionais da pesquisa como parte do projeto global Worlds of Journalism apresentam evidências de que meios distintos não oferecem condições de trabalho diferentes nem modelos profissionais alternativos para os seus jornalistas. Os resultados revelam ainda que a cultura profissional depende da interação entre valores pessoais e das pautas de organizações e empresas. Nesse sentido, o artigo se propõe a abordar o estudo de cultura jornalística com base em uma perspectiva multidimensional que analise os marcos legais, a proteção sindical, as pautas organizacionais e os códigos de ética profissional. Las prácticas profesionales de los periodistas argentinos dan cuenta de la multiplicidad de factores que impactan en la cultura periodística. El resultado del estudio nacional para el proyecto global Worlds of Journalism ofrece evidencias de que el tipo de medios en los que se desempeñan no genera condiciones de trabajo diferentes ni responde a modelos profesionales alternativos. Los resultados refuerzan el enfoque de que la cultura profesional es resultado de la interacción entre valores personales y las pautas de las organizaciones y empresas. En ese sentido, se plantea la necesidad de abordar el estudio de la cultura profesional del periodismo desde una perspectiva multidimensional que incluya el estudio de los marcos legales, la protección gremial, las pautas organizacionales y los parámetros éticos aceptados.